Different Interpretations given by Judicial Practice to Exceptions that can be Invoked in the Procedure due to the Wealth Research Commission - Gradinaru, Sandra (Acta Universitatis Danubius. Juridica, 2023)
The legal framework of the procedure before the Wealth Research Commission is regulated by Chapter II, respectively the provisions of art. 10-15 and Chapter V Final provisions of Law no. 115/1996, for the declaration and control of the assets of dignitaries, magistrates, persons with management and control functions and of civil servants, published in the Official Gazette Part I no. 263 of 28/10/1996. In chapter V, art. 31 it is expressly provided that the provisions of Law no. 115/1996 are completed with the provisions of the Code of Civil Procedure and with those regarding the execution of budgetary receivables. Thus, in the procedure carried out before the Research Commission, the provisions of the Code of Civil Procedure are applied. This conclusion was not unanimously appropriated by the national courts and there are opposing views in the sense that the provisions of the Code of Civil Procedure would apply truncated, the procedure before the Commission for the Investigation of Assets is not a judicial one, but a purely administrative one. In this paper we will demonstrate that before the Commission for the Research of assets can be invoked including exceptions specific to a judicial procedure, otherwise being circumvented the imperative provisions of law 115/1996. We consider it within the competence of the Wealth Research Commission to resolve exceptions such as the prescription of the right of the National Integrity Agency to issue the Evaluation Report of the investigated person and of his right to notify The Wealth Research Commission, except for the nullity of the documents drawn up by the integrity inspectors in the absence of information and summons of the investigated person, the research of the legality of the random distribution of the integrity inspectors who prepared the Evaluation Report, as well as procedural incidents related to the incompatibility of members of the Wealth Research Commission.